Experimental Study of Pre-Tensioned Polygonal Prestressed T-Beam Under Combined Loading Condition - Yao, Zengbo; Wei, Mingguang; Yan, Hai; Yu, Dinghao; Li, Gang; Zhang, Chunlei; Tao, Jinglin; Pei, Huiteng (Buildings (Basel), 2025)
In order to investigate the mechanical behavior of a novel pre-tensioned polygonal prestressed T-beam subject to combined bending, shear, and torsion, this study meticulously designed and fabricated a full-scale specimen with a calculated span of 28.28 m, a beam height of 1.8 m, and a top flange width of 1.75 m. A systematic static loading test was conducted. A multi-source data acquisition methodology was employed throughout the experiment. A variety of embedded and external sensors were strategically arranged, in conjunction with non-contact digital image correlation (VIC-3D) technology, to thoroughly monitor and analyze key mechanical performance indicators, including deformation capacity, strain distribution characteristics, cracking resistance, and crack propagation behavior. This study provides valuable insights into the damage evolution process of novel polygonal pre-tensioned T-beams under complex loading conditions. The experimental results indicate that the loading process of the specimen when subjected to combined bending, shear, and torsion, can be divided into two distinct stages: the elastic stage and the crack development stage. Cracks initially manifested at the junction of the upper flange and web at the extremities of the beam and at the bottom flange of the loaded segment. Subsequently, numerous diagonal and flexural–shear cracks developed within the web, while diagonal cracks also commenced to form on the top surface, exhibiting a propensity to propagate toward the support section. Following the appearance of diagonal cracks in the web concrete, both stirrup strain and concrete strain demonstrated abrupt changes. The peak strain observed within the upper stirrups was markedly greater than that measured in the middle and lower regions. On the front elevation of the web, the principal strain peak was concentrated near the connection line between the loading bottom and the upper support. In contrast, on the back elevation of the web, the principal tensile strain was more pronounced near the connection line between the loading top and the lower support.